In situ stress analysis in the Yinggehai Basin, northwestern South China Sea: Implication for the pore pressure-stress coupling process. (November 2016) - Liu, Rui; Liu, Jianzhang; Zhu, Weilin; Hao, Fang; Xie, Yuhong; Wang, Zhengfeng; Wang, Lifeng
Abstract: The Yinggehai Basin is located in the triangle between the Sunda block, South China block, and the South China Sea and is an interesting target for in situ stress investigation, not only because of its specific tectonic position but also due to its abnormally high pore pressures. Magnitudes and orientations of in situ stress were directly constrained by measurements operated in the vertical boreholes that were drilled in the Yinggehai Basin. Gradients and magnitudes of the least horizontal stress remarkably increase with overpressure enhancement, indicating that the least principal stress and pore pressure are in fact coupled. The ratios of pore pressure/stress coupling (ΔƠh /ΔPp ) are similar in the north and south central Yinggehai Basin, despite the burial depths of overpressure top are different. However, a deeply buried strike-slip faulting regime under WNW-ESE oriented horizontal compression was identified in the central Yinggehai Basin, where the ΔƠh/ΔPp ratios have intermediate values, ranging from that for an idealized normal faulting stress regime to that for the southeastern South China (a strong strike-slip or even reverse faulting stress regime). Additionally, the WNW-ESE orientations of maximum horizontal stress determined from drilling-induced tensile fractures in the Yinggehai Basin are inappropriate for the present maximum horizontal stress derived from earthquake focal mechanism solutions in the northern segment of the Red River Faults, suggesting that the dextral movement of Red River Faults has slightly influenced the present stress state in the Yinggehai Basin. The present stress state of the Yinggehai Basin was primarily generated by the ESE absolute horizontal motion of the Sunda and South China blocks. Highlights: In situ stress in the triangle between the Sunda, South China, and the South China Sea. The pore pressure-stress coupling ratio in the strike-slip faulting regime. Present stress state of Yinggehai Basin was generated by the motion of Sunda, South China.